Optimising Project Team Management in the CAD/CAE Engineering Services Sector for the Automotive Industry - Lichtarski, Marcin (Optymalizacja zarządzania zespołami projektowymi w sektorze usług inżynieryjnych CAD/CAE dla przemysłu motoryzacyjnego, 2025)
Optimising project team management in the CAD/CAE engineering services sector for the automotive industry aims to enhance efficiency and reduce costs in dynamic environments. Building technically skilled, flexible, and cost-effective teams remains a key challenge. This article presents a framework based on qualitative and quantitative research, focusing on leadership, diversity, and technological integration. The study hypothesizes that competence matrices and optimisation solvers improve efficiency and reduce delivery costs. Empirical research at Endego sp. z o.o. confirms the value of balancing team experience with costs to maximize operational performance. The findings highlight the importance of dynamic management, collaboration, and ongoing employee development. Optimisation tools that leverage competency and cost data enable real-time team adjustments, improving results while minimizing expenses. Future improvements, such as integrating live project data and using tools like the Cooperation Grade Matrix to measure team cohesion, are also recommended. Ultimately, investing in advanced optimisation solutions is essential for maintaining flexibility, innovation, and excellence in CAD/CAE project management.
Quote as: Lichtarski, M. (2025). Optimising Project Team Management in the CAD/CAE Engineering Services Sector for the Automotive Industry. In A. Witek-Crabb & J. Radomska (Eds.), New Trends in Business Management. Strategy, Branding, Teamwork (pp. 137-155). Publishing House of Wroclaw University of Economics and Business.
Keywords: optimisation; efficiency; cost reduction; competence matrices; team cohesion; optymalizacja; efektywność; redukcja kosztów; matryce kompetencji; spójność zespołu